Aspergillus niger as a Secondary Metabolite Factory - Yu, Ronglu; Liu, Jia; Wang, Yi; Wang, Hong; Zhang, Huawei (Frontiers in Chemistry, 2021)
Aspergillus niger, one of the most common and important fungal species, is ubiquitous in various environments. A. niger isolates possess a large number of cryptic biosynthetic gene clusters (BGCs) and produce various biomolecules as secondary metabolites with a broad spectrum of application fields covered agriculture, food and pharmaceutical industry. By extensive literature search, this review makes a comprehensive summary on biological and chemical aspects of A. niger strains including their sources, BGCs and secondary metabolites as well as biological properties and biosynthetic pathways. Future perspectives in the discovery of more A. niger-derived functional biomolecules are also provided in this review